2009
DOI: 10.1002/ijc.24561
|View full text |Cite
|
Sign up to set email alerts
|

Modified heparins inhibit integrin αIIbβ3 mediated adhesion of melanoma cells to platelets in vitro and in vivo

Abstract: The adhesion of tumor cells with platelets is important in the process of tumor metastasis. A huge work has indicated that antiadhesion is an effective strategy for metastasis inhibition. In this article, we assess the role of platelet integrin a IIb b 3 in adhesion of melanoma cells to platelets and the effects of heparin and modified heparins on the adhesion in vitro and in vivo. We show that platelet integrin a IIb b 3 is involved in the interaction of human melanoma A375 cells with platelets, and the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
2
25
0
1
Order By: Relevance
“…In fact, previous studies, performed with radioactive or fluorescent heparin derivatives showed that these compounds were bound and internalized by SMC (20), human endothelial cells (21) and rat neurons (33). Other reports show that heparin binds to specific cell surface adhesion molecules, for example, integrins to modulate the adhesive capabilities of different cell lines (34,35). The present study clearly demonstrates that M5 melanoma cells uptake heparin which results in its cytoplasmic and nuclear localization.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In fact, previous studies, performed with radioactive or fluorescent heparin derivatives showed that these compounds were bound and internalized by SMC (20), human endothelial cells (21) and rat neurons (33). Other reports show that heparin binds to specific cell surface adhesion molecules, for example, integrins to modulate the adhesive capabilities of different cell lines (34,35). The present study clearly demonstrates that M5 melanoma cells uptake heparin which results in its cytoplasmic and nuclear localization.…”
Section: Discussionsupporting
confidence: 72%
“…Phosphorylation of this tyrosine initiates a cascade of signal transduction events that renders the molecule a fully active kinase, able to initiate the formation of mature focal kinase complexes and capable adhesion (25). Heparin is previously shown to interfere with the function of integrin adhesion receptors during the selectin or VCAM-1 dependent attachment of melanoma cells (26,27). We hypothesized that heparin may affect the adhesive/migratory functions of FAK (28), the other major component of the focal kinase complexes.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previously, we demonstrated that the preincubation of tumor cells with a β3 integrin-blocking antibody inhibited the indirect adhesion between tumor cells and platelets (19). In the present study, we investigated the contribution of β3 integrins, expressed in platelets, as well as β3 and β1 integrins, expressed in tumor cells.…”
Section: Fibrinogen Bridges the Indirect Adhesion Between Tumor Cellsmentioning
confidence: 82%
“…However, the hemorrhagic dangers caused by the marked anticoagulant effect of heparin has limited its application as an anti-metastatic drug. Previously, we demonstrated that certain chemically modified heparins with low anticoagulant activity were capable of blocking the P-selectin and αⅡbβ3 integrin-mediated adhesion of platelets and tumor cells (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…The Role of Adhesion Receptors in Melanoma Metastasis and Therapeutic Intervention Thereof 397 heparin has also an inhibitory capacity to this binding (Zhang et al, 2009). Thrombin, interacting with its receptor PAR-1 on melanoma cells (protease-activated receptors-1) has a strong impact for regulating this interaction.…”
Section: Integrins As Targets For Heparinmentioning
confidence: 99%